The sultan's communists : Moroccan Jews and the politics of belonging - Heckman, Alma Rachel (Stanford studies in Jewish history and culture, 2021)
"A history of Jews in Morocco from the 1930s through the 1970s, this book traces how Jewish communists went from being outsiders (even pariahs) vis-à-vis the Makhzan to being embraced as the "Sultan's communists." Her narrative offers welcome nuance to our understanding of how Jews in Morocco were and are viewed--by their non-Jewish neighbors, by the Moroccan government, by American Jewish organizations, and even by tourists and scholars."